2017
DOI: 10.1590/1981-22562017020.160183
|View full text |Cite
|
Sign up to set email alerts
|

Elderly patients with facial trauma: a 10 year review

Abstract: Objective: to analyze the epidemiological profile of geriatric patients with facial trauma treated at a Maxillofacial Surgery Department in southern Brazil over a period of 10 years. Methods: a retrospective analysis of the medical records of patients aged over 60 years treated for facial trauma in the period from January 2001 to December 2010 was performed. Result: of a total of 1,385 analyzed medical records of patients with facial trauma, 86 (6.2%) belonged to the group aged 60-89 years. The male gender was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
(17 reference statements)
1
4
1
1
Order By: Relevance
“…In a study on elderly population road traffic accidents were most common cause of injury in population with age range 60-69 years, while in patients older than 70 falls were the most common cause of injury. 12 These findings are in contrast to another study where predominant cause of injury in older population were falls and more than 50% of the fractures were caused by falls, followed by RTA; industrial injuries and assault related injuries rarely occurred. 16 According to another study conducted in Australia the predominant cause of facial injuries in older population was falls.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In a study on elderly population road traffic accidents were most common cause of injury in population with age range 60-69 years, while in patients older than 70 falls were the most common cause of injury. 12 These findings are in contrast to another study where predominant cause of injury in older population were falls and more than 50% of the fractures were caused by falls, followed by RTA; industrial injuries and assault related injuries rarely occurred. 16 According to another study conducted in Australia the predominant cause of facial injuries in older population was falls.…”
Section: Discussioncontrasting
confidence: 77%
“…8 Among all mechanisms of injury males are more commonly affected by trauma. 12 The present study also shows a male predominance as 67.5% of the patients were males. These results are in consistent with a study that was conducted in a Malaysian Hospital on total 134 patients who were 60 years of age or older were, there were 101 (74.5%) men and 33(24.6 %) women.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…19,24,27,33 In addition, for any particular type of fall, skeletal injuries tend to have greater consequences in older patients than in younger patients. 23,25 Reductions in bone mass linked to osteoporosis or other changes in bone metabolism increase the susceptibility to fractures in the elderly, including the maxillofacial area.…”
Section: Ta B L Ementioning
confidence: 99%
“…12 With this trend in the global elderly population, traumatic injuries in this group will also increase, including those affecting the maxillofacial area, with a heavier load on health systems. Although there have been epidemiologic studies on maxillofacial fractures in the elderly population among Asian, [13][14][15][16][17][18] African, 19 American, [20][21][22][23][24] Australian 25 and European [26][27][28][29][30] patients, these studies are infrequent, often monocentric and retrospective. Notably, Possebon et al 24 reported that an epidemiological understanding of maxillofacial trauma is necessary to improve the management of ageing populations, to prevent accidents, to enhance the quality of life and to reduce public spending on the treatment of such trauma.…”
Section: Introductionmentioning
confidence: 99%